Effectiveness of Problem-Based Learning with the Teaching at the Right Level Approach on Students' Mathematical Concepts Understanding Ability - Juika Juika; Sinta Verawati Dewi; Yeni Heryani (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
Mathematical concept comprehension ability reflects students' proficiency in restating mathematical ideas and applying them in various contexts. This study aims to describe the results of problem-based learning combined with the Teaching at the Right Level (TaRL) approach on the mathematical concept understanding ability of junior high school students. This research uses a quantitative method with a pre-experimental design of the One-Shot Case Study type. The research subjects are students from class VIII-K of SMP Negeri 8 Tasikmalaya, who were selected purposively. Data was collected through essay tests that had been validated for content and reliability. The analysis results show that the data is normally distributed and the obtained t-value is greater than the t-table value (3.534 > 1.697), indicating that problem-based learning with the TaRL approach yields learning outcomes that exceed the learning achievement criteria (KKTP). These findings indicate that an integrative problem-based learning model with TaRL has the potential to improve students' understanding of mathematical concepts across various ability levels.